2018
DOI: 10.3389/fmed.2017.00244
|View full text |Cite
|
Sign up to set email alerts
|

Functional Capacity and Levels of Physical Activity in Aging: A 3-Year Follow-up

Abstract: Over the last decades, the world elderly population has increased exponentially and this tendency will continue during the coming years; from 2000 to 2050, people over 60 will double and those over 80 will quadruple. Loss of independence occurs as people age due to mobility restrictions, frailty, and decreased functional fitness and cognitive abilities. Evidence has shown that appropriate programs and policies contribute to keep older adults healthy and independent over time. The purpose of this chapter is to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
45
1
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(69 citation statements)
references
References 46 publications
7
45
1
10
Order By: Relevance
“…Secondly, in this study, functional ability was determined to be greater in those people who engaged in high physical activity compared to those who participated in moderate activity. These results are in line with the existing literature showing an improvement in physical health regarding functional skills in those older adults who practiced high physical activity [8][9][10][11]. On the other hand, some studies [29] have also indicated that there is a relationship between low autonomy and poor physical activity; however, some of these studies have not gone far enough into the amount and type of physical practice required for such a result.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Secondly, in this study, functional ability was determined to be greater in those people who engaged in high physical activity compared to those who participated in moderate activity. These results are in line with the existing literature showing an improvement in physical health regarding functional skills in those older adults who practiced high physical activity [8][9][10][11]. On the other hand, some studies [29] have also indicated that there is a relationship between low autonomy and poor physical activity; however, some of these studies have not gone far enough into the amount and type of physical practice required for such a result.…”
Section: Discussionsupporting
confidence: 89%
“…In this regard, physical activity is one of the most important resources to improving health and quality of life in older adults, which has been revealed by different studies [6][7][8]. In addition to this, many authors have shown that physical activity improves the functional abilities of older adults [9][10][11] as well as their quality of life [12]. In a combined intervention study of physical activity and cognitive stimulation carried out in a sample of 50 older adults where 44 were women [13], an improvement in the functional abilities and activities of daily living were observed.…”
Section: Introductionmentioning
confidence: 99%
“…An assessment of the functional state of body and its reserve capacities is important for determining the effectiveness of physical education classes [16,17]. Good functional state can be considered as a prerequisite for high physical working efficiency and potential ability of the body to adapt to physical activity [10,18].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, particularities, such as the level of functional capacity, must be followed according to the ACSM recommendations (20), particularly for elderly people (21). The need to perform physical activity is as evident as the need to guarantee the necessary security of its practitioners.…”
Section: Pre-exercise Screeningmentioning
confidence: 99%